2017
DOI: 10.1007/s11011-017-0101-6
|View full text |Cite
|
Sign up to set email alerts
|

Mutation in the AGK gene in two siblings with unusual Sengers syndrome

Abstract: Sengers syndrome is a rare autosomal recessive metabolic disorder caused by lack of acylglycerol kinase due to mutations in the AGK gene. It is characterized by congenital cataract, hypertrophic cardiomyopathy, myopathy and lactic acidosis. Two clinical forms have been described: a severe neonatal form, and a more benign form displaying exercise intolerance. We describe two siblings with congenital cataract, cardiomyopathy, hypotonia, intellectual disability and lactic acidosis. Whole exome sequencing revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…All rights reserved Sengers syndrome is an autosomal recessive disorder characterised by congenital cataracts, hypertrophic cardiomyopathy, skeletal myopathy and lactic acidosis ( Table 1) [ [107][108][109][110][111][112][113][114][115]. Sengers syndrome is caused by a variety of mutations in the TIM22 complex component AGK, including missense, nonsense and frameshift mutations [107][108][109][110][111][112][113][114][115]. The severity of the phenotype varies significantly, even within families with the same mutation, although it should be noted that the less affected sibling in this case received intervention at an early age potentially affecting disease progression [113].…”
Section: Accepted Articlementioning
confidence: 99%
See 1 more Smart Citation
“…All rights reserved Sengers syndrome is an autosomal recessive disorder characterised by congenital cataracts, hypertrophic cardiomyopathy, skeletal myopathy and lactic acidosis ( Table 1) [ [107][108][109][110][111][112][113][114][115]. Sengers syndrome is caused by a variety of mutations in the TIM22 complex component AGK, including missense, nonsense and frameshift mutations [107][108][109][110][111][112][113][114][115]. The severity of the phenotype varies significantly, even within families with the same mutation, although it should be noted that the less affected sibling in this case received intervention at an early age potentially affecting disease progression [113].…”
Section: Accepted Articlementioning
confidence: 99%
“…Sengers syndrome is an autosomal recessive disorder characterised by congenital cataracts, hypertrophic cardiomyopathy, skeletal myopathy and lactic acidosis (Table 1) [107][108][109][110][111][112][113][114][115]. Sengers syndrome is caused by a variety of mutations in the TIM22 complex component AGK, including missense, nonsense and frameshift mutations [107][108][109][110][111][112][113][114][115].…”
Section: Agk and Sengers Syndromementioning
confidence: 99%
“…Supplementary Material 1 | Gene structure of AGK and localization of identified mutations (1)(2)(3)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Red font indicates newly reported mutations.…”
Section: Data Availability Statementmentioning
confidence: 99%
“…The AGK gene is located on chromosome 7q34 and consists of 16 exons (1). To date, several studies have identified different types of loss-of-function mutations in the AGK gene, including start codon mutations, nonsense, frameshift, and splice site mutations (1)(2)(3)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). AGK is a mitochondrial protein that catalyzes the phosphorylation of diacylglycerol (DAG) and monoacylglycerol (MAG) to phosphatidic acid (PA) and lysophosphatidic acid (LPA), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, and although AGK was not yet described as a component of the TIM22 complex, decreased levels of Adenine nucleotide transporter 1 (a metabolite carrier) were reported for Sengers syndrome patients [ 101 , 190 ]. Additional studies in patients presenting with various forms of this syndrome, identified already described or new mutations in the AGK gene (p.M1I, p.K327*, p.I175Yfs*2, c.424-1G>A, p.R137*, p.I346Yfs*39, p.L75Qfs*12, p.R281*, p.Q291*, c.877+3G>T, p.Q291*, p.F406Vfs*4) [ 102 , 103 , 104 , 105 ]. Two independent studies characterized AGK as a component of the TIM22 complex and showed that this lipid kinase was required for proper metabolite carrier import into the inner membrane [ 167 , 168 ].…”
Section: Defects In Carrier Transport Associated With Diseasementioning
confidence: 99%